2020
DOI: 10.1371/journal.pone.0232782
|View full text |Cite
|
Sign up to set email alerts
|

The role of viral particle integrity in the serological assessment of foot-and-mouth disease virus vaccine-induced immunity in swine

Abstract: The efficacy of foot-and-mouth disease virus (FMDV) inactivated vaccines is mainly dependent on the integrity of the whole (146S) viral particles. If the intact capsids disassemble to 12S subunits, antibodies against internal-not protective epitopes, may be induced. Serological correlates with protection may be hampered if antibodies against internal epitopes are measured. Here we compared the performance of different ELISAs with the virus-neutralization test (VNT) that measures antibodies against exposed epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Notably, the FMDV VNT titers elicited by VLP L-B/N-T in mice and pigs, were considerably higher than those previously reported for immunization with dendrimeric peptides affording full protection against FMDV challenge [ 33 , 34 , 35 , 37 ], as well as those elicited by current chemically inactivated whole-virus vaccines in pigs and cattle [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 74%
“…Notably, the FMDV VNT titers elicited by VLP L-B/N-T in mice and pigs, were considerably higher than those previously reported for immunization with dendrimeric peptides affording full protection against FMDV challenge [ 33 , 34 , 35 , 37 ], as well as those elicited by current chemically inactivated whole-virus vaccines in pigs and cattle [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 74%
“…We provided data to support the idea that cross-serotype reactive responses were due in part to the binding of test sera to internal capsid epitopes, although the reactivity of some sera indicated that external capsid epitopes may also contribute. Degraded vaccines gave rise to cross-reactive antibodies that fail to provide good protection [ 8 , 9 ], but that may be especially cross-reactive in ELISAs. This can cause problems in the use of SP-ELISAs as indicators of protection in vaccinated animals and may account for the poor correlation that is sometimes seen between SP-ELISAs and VNT, not only in estimates of protection but also cross-protection [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the FMDV capsid readily dissociates, for example, if vaccine cold chains are not strictly maintained, it is likely that the antigen presented to the host following infection or vaccination, as well as that on ELISA plates, will be a mixture of intact capsids on which only external surface epitopes are exposed and viral subunits presenting external and internal capsid epitopes. This will give rise to a variable ratio of serotype-specific and protective antibodies on the one hand and serotype-independent and non-protective antibodies on the other hand [ 8 , 9 ]. To enhance their stability and to reduce their susceptibility to heat and pH changes, recombinant empty viral capsids were engineered as putative vaccines with stabilizing mutations at the capsid subunit interphases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of the buffalo population is found in the North-Eastern provinces of Formosa and Corrientes (13), within the FMD-free with vaccination zone and close to the border with Paraguay, where the latest regional FMDV-type O outbreak occurred in 2011 (14). They are compulsory vaccinated following the same campaign designed for cattle, twice a year during the first 2 years of age, and once a year thereafter (15)(16)(17). The vaccine used is oil-based and contains four viral stains (A24/Cruzeiro, O1/ Campos, C3/Indaial and A7Argentina/2001).…”
Section: Introductionmentioning
confidence: 99%